Engaging Mathematics Through Computer Games - Ayazhan Turdyzhan (Research Retrieval and Academic Letters, 2025)
The teaching strategy followed the academic calendar by including computer games specifically designed for the seventh grade into regular class sessions. The objectives included showcasing the value of gamification in homework assessment and encouraging a thorough comprehension of maths subjects through interactive gaming. The instruction’s goals were to bridge the gap between traditional and current assessment methods, improve students’ math engagement and comprehension, and dynamically evaluate assignment comprehension by immersing students in math-based activity.